Digital Marketing dan Performa Bisnis Kuliner: Studi pada Warung Gongso Tuan Muda di Kabupaten Sleman, Yogyakarta - Della Ayunda Putri Pratama (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study analyzes the business performance of Warung Gongso Tuan Muda in Sleman Regency, Yogyakarta, from marketing, operational, human resource, and financial perspectives, and evaluates the implementation and effectiveness of online marketing strategies and social media use. Using descriptive qualitative method with data collection through observation, interviews, and analysis of sales and financial reports from January to August 2025, the results showed positive performance growth with 177% revenue increase and cumulative profit of IDR 42.5 million. Digital marketing strategies through GoFood, GrabFood, and ShopeeFood platforms, along with influencer collaboration, significantly increased brand awareness and sales. However, promotional effectiveness can still be improved through more efficient budget management, data-based evaluation, and social media content innovation. Operations and human resources run efficiently with adaptive workforce support and performance-based reward systems. Financial conditions show stability and strong growth potential for business sustainability. This study recommends strengthening analytics-based marketing strategies and consistency in digital content publication. For culinary SMEs, integration between online promotion and offline services is a key success factor.